(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Pratama SM, Wajizah S, Wahyudi I, Ilham, Zulfahrizal, Munawar AA, Samadi. 2025. The effect of fermented cacao pod husk using Phanerochaete chrysosporium on nutritive value, digestibility, fermentation parameters, and methane emissions. Asian J Agric 9: 276-287. This research aimed to study the effect of fermentation using Phanerochaete chrysosporium with different incubation times on nutritive value, digestibility, fermentation parameters, and methane emissions of cacao pod husk. The treatments tested were: F0: without incubation; F1: 7 days of incubation time; F2: 14 days of incubation time; F3: 21 days of incubation time and F4: 28 days of incubation time. The variables observed were the quality of nutritional value, fiber fraction, in vitro rumen digestibility, gas production and methane gas concentration. The results showed that the treatment increased the crude protein value, reduced crude fiber and increased the Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF) values as the incubation period increased. Treatment effectively increased digestibility with the highest obtained at F4 and the lowest at F1. The treatment also increased the total ammonia (NH3-N) and Volatile Fatty Acid (VFA) concentrations in the rumen with a pH that was still within normal levels. The total concentration of VFA or NH3 in F4 was higher than in other treatments. The gas production value and methane gas concentration can be reduced by P. chrysosporium treatment with an incubation time of up to 28 days. It was concluded that the nutritional quality and digestibility of cocoa pod husk could be improved but were still relatively low, even though the pH, NH3-N and VFA Total values were in the normal range.